153 Relationship between micro RNA-145 and vascular smooth muscle cell senescence in diabetes. (June 2018) - Hemmings, Karen; Riches-Suman, Kirsten; Turner, Neil; Karen, Porter; O'Regan, David
Abstract : Introduction: Saphenous vein (SV) graft failure after coronary bypass surgery is a significant problem in Type 2 diabetic (T2DM) patients, characterised by aberrant smooth muscle cell (SMC) remodelling. SV-SMC cultured from diabetic patients express elevated levels of microRNA-145, exhibit distinct morphology, impaired proliferation and DNA damage. This study explored a potential relationship between miR-145, DNA damage response signalling (DDR) and SV-SMC senescence. Methods: Using native human non-diabetic (ND) and T2DM-SMC, DDR signalling proteins (ATM, ATR, p21) were measured (real-time PCR) and subsequently quantified in ND cells overexpressing miR-145 (premiR-145 transfection). Conditioned medium (CM) from miR-145 overexpressing cells was analysed by ELISA for indicators of a senescence associated secretory phenotype (SASP) and to explore intracellular signalling (immunoblotting) in naïve ND-SMC. The effect of siRNA knockdown or pharmacological inhibition of ATM/ATR on cell proliferation was also explored (cell counting). Results: Increased expression of ATM, ATR and p21 was observed in T2DM-SMC relative to ND-SMC (n=8, p<0.05). MiR-145 overexpression increased ATR (n=7, p<0.01), and a trend to increased p21 was observed. Secretion of IL-6, IL-8 and MCP-1 was increased by 1.5, 2.0 and 5.5-fold, respectively (n=8, p<0.01) in miR-145-overexpressing cells; this CM induced persistent (≥96h) p38α phosphorylation in naïve cells. Pharmacological inhibition or gene-silencing of ATR, but not ATM significantly inhibited cell proliferation (n=4, p<0.05). Conclusion: Aberrant expression of DDR proteins in T2DM-SMC can be mimicked, at least partially by miR-145 overexpression. MiR-145 drives a SASP, resulting in chronic p-38 phosphorylation. MiR-145 holds potential as a therapeutic target to ameliorate SMC senescence.